Abstracta precisión Suiza - Barbero Sarzabal, Hernán (2003)
Remodelación casa La casona, del arq. Eric Frei, en Victoria, 2000.
Keywords: ARGENTINA; REMODELACION; VIVIENDAS UNIFAMILIARES; ENTRE RÍOS; VICTORIA; FREI, ERIC; RECICLAJE